Verification And Validation Of Buildingexodus Based On The Walking Speed Of People With Disabilities (PWD) - Lee, Sze Yee (Universiti Sains Malaysia, 2018)
People with disabilities (PWD) are often overlooked in building design although they are more vulnerable to hazards and face greater difficulties in accessing buildings such as train stations. The presence of PWD has a significant influence on pedestrian flow due to their slow walking speed, high space requirements and grouping tendencies, but their behaviours are rarely explored in pedestrian simulation models due to lack of empirical data. In an effort to accurately represent the behaviours of PWD in the buildingEXODUS pedestrian simulation model, this study aims to verify the core abilities of buildingEXODUS; conduct an experiment involving different types of PWD based on a train station layout; and validate buildingEXODUS’ capacity to simulate PWD. Verification of the model was done using selected standard tests from the National Institute of Standards and Technology (NIST). Seven categories of blind and wheelchair-bound people were studied, namely blind, blind with an able-bodied assistant, two-blinds, three-blinds, electric wheelchair, manual wheelchair and manual wheelchair with assistance. The walking speed and egress time of PWD with and without the presence of normal people was then determined from the experiment. Using the data collected, the experiment scenario was recreated in buildingEXODUS. The simulation egress time was then compared with the experimental egress time to validate buildingEXODUS. Overall, buildingEXODUS was able to represent the selected main core components of evacuation models that were scrutinised in the NIST verification tests. Experiment results indicated that the walking speed and egress time of sighted individuals were negatively influenced by the presence of other pedestrians. Subsequently, the ability of buildingEXODUS to simulate PWD was validated. The simulation can produce comparable results to real-life phenomena given that the occupant demographics are sufficiently understood.